Thermal Properties of Phosphorylated Nanodiamond Reinforced Polyimides - ÇAKMAKÇI, EMRAH; KAHRAMAN, MEMET VEZİR (WILEY, 2016)
Recently, the preparation of nanodiamond-polymer composites has attracted the attention of materials scientists due to the unique properties of nanodiamonds. In this study, novel polyimide (PI)/phosphorylated nanodiamonds (PNDs) composites were prepared. PNDs were achieved from the reaction of methylphosphonic dichloride with nanodiamonds in dichloromethane. Precursor of polyimide, which is the poly(amic acid) (PAA), was successfully synthesized with 3,30, 4,4'-benzophenonetetracarboxylic dianhydride and 4,4'-oxydianiline in the solution of N,N-dimethylformamide. Different ratios of phosphorylated nanodiamond particles were added into PAA solution and four different nanocomposite films were prepared. The amount of PNDs in the composite films was varied from 0 wt% to 3 wt%. The structure, thermal and surface properties of polyimide films were characterized by scanning electron microscopy (SEM), ATR-FTIR, thermogravimetric analysis (TGA), ultraviolet visible spectroscopy, and contact angle. SEM and FTIR results showed that the phosphorylated nanodiamond and PI/PNDs films were successfully prepared. Phosphorylated nanodiamonds were homogeneously dispersed in the polymer matrix and they displayed good compatibility. TGA results showed that the thermo-oxidative stability of PI/PNDs films was increased with the increasing amount of phosphorylated nanodiamond. (C) 2015 Society of Plastics Engineers
Keywords: NANOCOMPOSITES